2017
DOI: 10.1063/1.4994689
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of point defect concentration in Cu2ZnSnS4: Insights into the high-temperature equilibrium and quenching

Abstract: Herein we study the native point defect equilibrium in Cu2ZnSnS4 (CZTS) by applying a statistical thermodynamic model. The stable chemical-potential space (SCPS) of CZTS at elevated temperature was estimated directly, on the basis of deviations from stoichiometry calculated for the different combinations of chemical potential of the components. We show that the SCPS is narrow due to high concentration of ( − − + ) complex which is dominant over other complexes and isolated defects. The CZTS was found to have p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The intrinsic CZTS is always p-type due to the large population of Cu Zn and V Cu acceptor defects. [75,76] However, due to the relatively deep acceptor level, a higher concentration of Cu Zn defects is considered detrimental to device performance. [75,77] Preparing CZTS films under Cu-poor and Zn-rich environments can promote more ideal V Cu generation.…”
Section: Point Defectsmentioning
confidence: 99%
“…The intrinsic CZTS is always p-type due to the large population of Cu Zn and V Cu acceptor defects. [75,76] However, due to the relatively deep acceptor level, a higher concentration of Cu Zn defects is considered detrimental to device performance. [75,77] Preparing CZTS films under Cu-poor and Zn-rich environments can promote more ideal V Cu generation.…”
Section: Point Defectsmentioning
confidence: 99%
“…I would suggest that you insert one or two sentences about Cu/Zn disorder in kesterites before you start with "our goal". The CZTSSe materials have been thoroughly investigated through theoretical calculations specifically to determine the nature of defects (and their concentration) which could explain their semiconducting properties 29,30 . These studies demonstrated that at the thermodynamic equilibrium for the stoichiometric Cu2ZnSnS4 composition, many defects in high concentration may exist in this material.…”
Section: Cationic Disorder In Czts Materialsmentioning
confidence: 99%
“…Comparing CZTS to the Cu(In/Ga)S 2 (CIGS) absorber material, CZTS often suffers from a high open-circuit voltage (V OC ) deficit [7−9] larger than 0.6 eV, low external quantum efficiency (EQE) in the long wavelength region, low carrier lifetime, and thus fill factor [10] . These observations are commonly attributed to the abundance of point defects and defect complexes [11,12] , band edge or electrostatic potential fluctuation induced by defect compensation [13] , interface defects [14,15] , unfavorable band alignment [16,17] and secondary phases due to composition inhomogeneity, and back contact decomposition [15,18] . Defect abundance in CZTS originates from the intrinsically low formation energy of point defects in thermodynamic limit [8,19] .…”
Section: Introductionmentioning
confidence: 99%